Controle fonte-dreno da mobilização de reservas na germinação e estabelecimento de plântulas de cajueiro (Anacardium occidentale L.) expostas à salinidade - Ponte, Luiz Ferreira Aguiar (2007)
In this work, the effects of NaCI-salinity on cotyledonary reserve mobilization were studied during the establishment of cashew seedlings (Anacardium occidentale L.). The cashew nuts were sown in saturated vermiculite and irrigated daily with distilled water (control) or 50 mM NaCI solution [...]